Kesetaraan Gender Dalam Pendidikan Menurut Pemikiran M. Quraish Shihab - Cahyawati, Inayah; Muqowim, Muqowim (UIR Press, 2022)
In modern times there is still inequality about the roles and positions held by men and women in society. This is still widely discussed and debated because women still have limited opportunities in various fields, especially in obtaining education. So according to M. Quraish Shihab there needs to be a grant of rights that are equal to men and always respect it so that there is no inequality or gender bias. Based on these problems, the writing of this article aims to gain knowledge and understanding of M. Quraish Shihab's views on gender equality in aspects of education and to know the need for the application of gender equality in education. Gender equality is a position where women and men get equal opportunities both in the family, society, nation, and state environment. From this library research obtained the result that M. Quraish Shihab strongly supports the right of women to get an education. He said that women and men deserve equal respect, but not all women and men alike. Getting a healthy education is a way to improve the quality of women and is also useful to educate children or offspring in the future so as to improve economic well-being which is one of the factors increasing the quality of a person's life. Through education, women can make changes that are useful for the advancement of women in various fields.